The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10098-017-1466-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative LCA of technology improvement opportunities for a 1.5-MW wind turbine in the context of an onshore wind farm

Abstract: This paper presents life cycle assessment (LCA) results of design variations for a 1.5-MW wind turbine due to the potential for advances in technology to improve their performance. Five LCAs have been conducted for design variants of a 1.5-MW wind turbine. The objective is to evaluate potential environmental impacts per kilowatt hour of electricity generated for a 114-MW onshore wind farm. Results for the baseline turbine show that higher contributions to impacts were obtained in the categories of ozone deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Replacing the elements with one of greater power would cause a change both in benefits (such as an increase in annual average productivity) and in costs. Costs would potentially be higher than in the case of a rotor of the same power because of an increase in the mass of the elements, and, as previous research has shown [10], the environmental impact of materials used to produce wind power plants is strongly related to their mass (greater mass = higher eco-indicator values). However, considering technological advances and developments in the construction of wind power plants, it is difficult to predict how, over the next 25 years, constructions, production methods, and the materials used to produce such objects will change, which means it is not possible to clearly determine how ecological costs and energy costs will change, the same being true for the values of the integrated efficiency indicators from ecological costs and energy costs.…”
Section: Efficieny Indicators From Ecological Costs and Energy Costs mentioning
confidence: 99%
See 1 more Smart Citation
“…Replacing the elements with one of greater power would cause a change both in benefits (such as an increase in annual average productivity) and in costs. Costs would potentially be higher than in the case of a rotor of the same power because of an increase in the mass of the elements, and, as previous research has shown [10], the environmental impact of materials used to produce wind power plants is strongly related to their mass (greater mass = higher eco-indicator values). However, considering technological advances and developments in the construction of wind power plants, it is difficult to predict how, over the next 25 years, constructions, production methods, and the materials used to produce such objects will change, which means it is not possible to clearly determine how ecological costs and energy costs will change, the same being true for the values of the integrated efficiency indicators from ecological costs and energy costs.…”
Section: Efficieny Indicators From Ecological Costs and Energy Costs mentioning
confidence: 99%
“…In a wider context, analyses have been conducted on the impact of wind farm lifecycles with the aid of the Life Cycle Assessment (LCA) method, including areas of potential impact on human health, the quality of the natural environment, and natural resources [6][7][8][9]. Analyses have also concerned the impact of the lifecycle of wind power plants on water and soil environment as well as their emissions into the atmosphere [10][11][12]. Many papers have also dealt with the aspects of the impact of particular elements and structural assemblies of wind power plants The lifespan of wind power plants is accepted to be 25 years and, in most cases, they are disassembled after 25 years [20,[43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Renewable power generation technologies can offer virtually no carbon emissions and are becoming increasingly cost competitive (Simons and Cheung 2016). In 2016, 165 GW renewable power capacity was implemented around the world, which accounted for approximately two-thirds of the total net new power capacity (Ozoemena et al 2018). This decrease in price has resulted in an increase in renewable generation technologies, particularly in solar photovoltaics (PV) and wind (IEA 2017).…”
Section: Relevant Literaturementioning
confidence: 99%
“…In comparison with fossil fuel, wind energy is a more environmentally friendly energy source, but also has social and environmental footprints with climate change implications [22]. There are projections for technology improvement opportunities (TIOs) in the manufacturing materials and processes for the wind farm industry, with particular respect to an onshore wind farm [23]. Nevertheless, whether the context is for an onshore or an offshore wind farm, it is necessary to pursue a better understanding of ways to enable a cleaner energy transition devoid of (or with very infinitesimal) GHG footprints like conventional fossil fuels [24].…”
Section: Wind Turbines and Ghg Emissionsmentioning
confidence: 99%